2013
DOI: 10.1038/modpathol.2013.93
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1 overexpression associated with E-cadherin and microRNA-200 downregulation is characteristic of undifferentiated endometrial carcinoma

Abstract: Undifferentiated endometrial carcinomas are very aggressive high-grade endometrial carcinomas that are frequently under-recognized. This study aimed to analyze the molecular alterations underlying the development of these endometrial carcinomas, focusing on those related to dedifferentiation. We assessed a series of 120 tumors: 57 grade 1 and 2 endometrioid endometrial carcinomas, 15 grade 3 endometrioid endometrial carcinomas, 27 endometrial serous carcinomas, and 21 undifferentiated endometrial carcinomas. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 36 publications
4
54
1
Order By: Relevance
“…34 Hence, it would appear that TAZ is a potent activator of cell transformation and tumorigenesis. 35,36 On the basis of this evidence, and given the importance of epithelial to mesenchymal transition and stemness in the carcinogenesis of certain subtypes of endometrial tumors, 3,4 we analyzed TAZ expression in a series of 143 endometrial carcinoma samples. We found that TAZ expression was associated with high-grade endometrial tumors, mainly represented by undifferentiated endometrial carcinomas and endometrial carcinosarcomas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…34 Hence, it would appear that TAZ is a potent activator of cell transformation and tumorigenesis. 35,36 On the basis of this evidence, and given the importance of epithelial to mesenchymal transition and stemness in the carcinogenesis of certain subtypes of endometrial tumors, 3,4 we analyzed TAZ expression in a series of 143 endometrial carcinoma samples. We found that TAZ expression was associated with high-grade endometrial tumors, mainly represented by undifferentiated endometrial carcinomas and endometrial carcinosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,21 We also analyzed 33 frozen samples of 17 low-grade endometrioid endometrial carcinomas and 16 endometrial carcinosarcomas. 21 Histological typing of all the samples was performed according to the World Health Organization (WHO) classification and the tissue samples were obtained from the Departments of Pathology at the Hospital Universitario Virgen del Rocío (Sevilla, Spain), Memorial Sloan-Kettering Cancer Center (New York, USA), and Hospital Universitari Arnau de Vilanova (IRBLLEIDA, Lleida, Spain).…”
Section: Tumor Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…ZEB1 overexpression and downregulation of miR-200s in these tumors was associated with absent or downregulated E-cadherin expression (Romero-Perez et al 2013). Upregulation of fascin, an actin binding protein, was recently suggested to represent an EMT like process in UECs and also contribute toward the invasive character of this aggressive EC subtype (Stewart & Crook 2015a).…”
Section: Emt Effectors and Core Regulators In Eec Progression And Metmentioning
confidence: 99%